Práticas e eventos de letramento no contexto da estratégia de saúde da família - Pereira, Rebeca Sales (2022)
My objective with this work is to analyze health literacy practices and events, in the context of the Family Health Strategy (FHS). The proposal presented is a congruence between the New Literacy Studies (NLS) and Critical Discourse Analysis (CDA), in its Dialectical-Relational aspect. To do so, I am based on the studies by Fairclough (2001, 2003), Chouliaraki and Fairclough (1999) and Magalhães, Martins and Resende (2017) regarding the theoretical-methodological framework of ADC; de Street (1984, 2014), Barton and Hamilton (1998), Baynham (1995), Barton, Hamilton and Ivanic (2000) and Heath (1982) on the NLS, among other authors. I carried out an ethnographic-discursive research (MAGALHÃES, 2000, MAGALHÃES; MARTINS; RESENDE, 2017) in a Basic Health Unit (BHU) in a neighborhood in the city of Fortaleza, using socioeconomic factors related to the Human Development Index of the State of Ceara. I used techniques of semi-structured interviews, focus groups and participant-observation, aiming at triangulating the discursive and non-discursive data of the investigated social practice. In the analysis, the categories belonging to the three meanings of discourse were used: actional, representational and identificational (FAIRCLOUGH, 2003), in addition to the categories belonging to the NLS: literacy practices (STREET, 1984) and literacy events (HEATH, 1982; HAMILTON, 2000).The results showed that the health professionals of the investigated BHU prioritize oral texts in the interaction with users, due to literacy difficulties related mainly to economic issues and the advanced age of the majority. Professionals use strategies, such as language adequacy (avoiding technical terms) and multimodality, to assist them in various literacy events, especially in medication administration, although the most effective strategy is the participation of family members as literacy mediators. Health education events, especially those held in groups that bring together risk groups, such as the elderly and pregnant women, bring relevant benefits to health promotion and disease prevention for educated and non-educated people. Discourses such as scientific, socio-historical, humanization and public policies, among others, are mobilized by social actors as ways of acting, representing (themselves) and self-identifying (-self), revealing, among other aspects, that power relations between professionals and users impede the effectiveness of some literacy events, especially consultations.